The Development Guidelines for Student Care and Support System of Pattananikom School - Saenmueang , Pongsathorn; Suksodkhieo, Worakarn (Journal of Dhamma for Life, 2025)
The purposes of the research were to determine 1) the Pattananikom School student care and support system and 2) the guidelines for student care and support system development. The population of this research was 90 Pattananikom School persons, as well as focus group discussions, was 7 participants. The research instruments were opinionnaires and focus group discussions. Frequency, percentage, means, standard deviation, and content analysis were applied for statistical data to report findings. The results of this research were as follows: 1. The Pattananikom School student care system was at a high level of overall results and total of each aspect by arranging means from the highest number to the lowest number, namely student development and encouragement, student prevention and correction, individual student awareness, student monitoring, and student transfer 2. The results of this research indicated that there were 6 strategies for the development guidelines for student care system of Pattananikom School as follows: 1) improving the systems for data collection and analyzing up-to-date data by utilizing information technology to store and analyze the data; 2) building trust between students and their advisors, and encouraging students to confidently share their information achieved by using techniques to foster good relationships and giving advice without any judgment; 3) developing the student care system to be clear and standardized for reducing the time spent on student screening process; 4) ensuring that the data used in the student screening process was completed, up-to-date, and accurately reflected the students’ current situations; 5) signing memorandums of understanding (MOUs) with external organizations to define the roles and responsibilities for supporting students systematically; and 6) improving the coordination systems and follow-up the results of student transfer by appointing a specific person taking responsible for this part.